Deep margin elevation, an option for post-endodontic rehabilitation: Case report - Navarrete-Olvera, Karla (Hasanuddin University, 2025)
ABSTRACT: Objective: This clinical report summarizes a procedure of deep margin elevation (DME), compatible technique with periodontal health and does not affect bond strength or other restorative properties.Methods: A female patient was presented with subgingival dystopalatine caries in tooth 21, we decided to perform DME, with the matrix in matrix technique and protocol adhesive with Obtibond FL®, cervical margin reconstruction with Harmonize® composite resin. Finally, root canal treatment was performed.Results: At follow-up 6 months the patient is clinical and radiographic asymptomatic. Conclusion: The rehabilitation of subgingival caries with DME technique in aesthetic areas is a favorable alternative, compatible with the periodontal health of the area.